Plunder & Protection Inc. - Halvor Mehlum; Karl Ove Moene; Ragnar Torvik (University of Oslo, Department of Economics, 2002)
When the state fails to supply basic security and protection of property, violent entrepreneurs not only seize the opportunity of plundering, but some also enter the protection business and provide protection against plunderers. This uncoordinated division of labor is advantageous for the entire group of violent entrepreneurs. Hence, in weak states a situation may arise where a large number of violent entrepreneurs can operate side by side as plunderers and protectors squeezing the producers from both sides. The problem reached new levels at the end of the cold war. As military forces were demobilized without civilian jobs to go to, many countries got an oversupply of qualiÞed violent people for crime, warfare and private protection. In this .market for extortion. the entry of new violent entrepreneurs enhances the proÞtability of them all. The supply of violence creates its own demand; an externality of violence that is detrimental to the development in poor countries.
Keywords: A10; 330; entrepreneurs; plundering; extortion; violence; Organisierte Kriminalität; Politisches System; Theorie